NILAI PENDIDIKAN KARAKTER DALAM LAGU-LAGU ANAK SEBAGAI MEDIA PEMBELAJARAN BIPA - Muhammad Yunus; M. Ridha Anwari; Istiqamah (STILISTIKA: Jurnal Bahasa, Sastra, dan Pengajarannya, 2022)
Character education is an important part in the world of education that functions to develop and shape the character and civilization of a dignified nation in order to educate the nation's life. One way to shape children's character is by introducing children's songs that contain positive values and moral messages in it. This study discusses the values of character education in children's songs which can also be a medium for BIPA learning. This study used descriptive qualitative method. The research results obtained are in line with what is needed in the research.